Inactivation of SARS‐CoV‐2 and HCoV‐229E in vitro by ColdZyme® a medical device mouth spray against the common cold. Issue 3 (14th October 2020) - Gudmundsdottir, Ágústa; Scheving, Reynir; Lindberg, Fredrik; Stefansson, Bjarki
Abstract: Background: The coronavirus disease 2019 (COVID‐19) pandemic calls for effective and safe treatments. Severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) causing COVID‐19 actively replicates in the throat, unlike SARS‐CoV, and shows high pharyngeal viral shedding even in patients with mild symptoms of the disease. HCoV‐229E is one of four coronaviruses causing the common cold. In this study, the efficacy of ColdZyme® (CZ‐MD), a medical device mouth spray, was tested against SARS‐CoV‐2 and HCoV‐229E in vitro . The CZ‐MD provides a protective glycerol barrier containing cod trypsin as an ancillary component. Combined, these ingredients can inactivate common cold viruses in the throat and mouth. The CZ‐MD is believed to act on the viral surface proteins that would perturb their entry pathway into cells. The efficacy and safety of the CZ‐MD have been demonstrated in clinical trials on the common cold. Method of Study: The ability of the CZ‐MD to inactivate SARS‐CoV‐2 and HCoV‐229E was tested using an in vitro virucidal suspension test (ASTM E1052). Results: CZ‐MD inactivated SARS‐CoV‐2 by 98.3% and HCoV‐229E by 99.9%. Conclusion: CZ‐MD mouth spray can inactivate the respiratory coronaviruses SARS‐CoV‐2 and HCoV‐229E in vitro . Although the in vitro results presented cannot be directly translated into clinical efficacy, the study indicates that CZ‐MD might offer a protective barrier against SARS‐CoV‐2 and a decreased risk of COVID‐19 transmission. Highlights: The ability of ColdZyme® (CZ‐MD), a medical device mouth spray, to inactivate coronaviruses (SARS‐CoV‐2 and HCoV‐229E) was tested using an in vitro virucidal suspension test (ASTM E1052). CZ‐MD mouth spray inactivated SARS‐CoV‐2 and HCoV‐229E in vitro by 98.3% and 99.9% respectively. The study indicates that CZ‐MD might offer a protective barrier against SARS‐CoV‐2 and a decreased risk of COVID‐19 transmission.